Benson's Relaxation Therapy to Reduce Postoperative Pain Intensity of TUR-P: A Case Study - Hidayah, Novita Dwi Nur (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Benign Prostate Hyperplasia (BPH) is a disease condition in which there is enlargement of the prostate gland. This study aims to conduct a case study by analyzing nursing care by providing benson relaxation therapy on pain levels in TUR-P postoperative patientsMethods: Research design using case studies. The respondents used were 3 postoperative TUR-P people with acute pain nursing problems. The intervention provided was Benson's relaxation therapy. The instrument used is a pain assessment sheet. Data was analyzed using descriptive analysisResults: The results showed the main complaints of lower abdominal pain, pain like being stabbed, pain intensity disappeared arising and pain scale 6. The nursing diagnosis that emerged in 3 patients was acute pain with pain management intervention. The implementation of benson relaxation is carried out for 15 minutes Decrease in pain level 6 to 5 on the first day, 5 to 4 on the second day and 4 to 3 on the third day.Conclusion: Benson's relaxation therapy can reduce acute pain in patients with postoperative TUR-P.